Gestión de ventas de la Boutique Kpriss en el Cantón La Troncal, provincia de Cañar en el periodo 2023. - Muñoz Zapata, Ashly Jael (2024)
This case study is called “Sales management of the Kpriss Boutique in the canton of La Troncal, province of Cañar in the period 2023 and has the objective of analyzing the sales management of the Kpriss Boutique in the canton of La Troncal, province of Cañar in the period 2023; The mixed approach, descriptive, bibliographic and analytical method was used as a methodology, the interview techniques carried out through the structured guide instrument, in addition, a documentary investigation was carried out that led to the design of a comparative matrix where the sales made were specified. in the period 2023; It is concluded that the sales criteria are not met because the sales processes were not established according to the stages that are part of sales management, the results of market segmentation are not the most optimal and the objectives are not achieved. sales projection goals because these are not made based on aspects such as the economic situation of Ecuadorians, microeconomic variables, historical data obtained from sales in previous years and under similar situations; It is recommended to share the data obtained in this research with the members of the sales team, to make known the importance of sales management, the stages that must be carried out according to the process diagram.